Butterworths international guide to money laundering : law and practice - Graham, Toby. (London ; Dayton, Ohio : Butterworths LexisNexis, 2003)
This book aimed at Money Laundering Reporting Officers ('MLRO'), compliance officers, senior approved under FSMA, lawyers and accountants. It will also be relevant to those who fall within the ambit of the Money Laundering Regulations , namely estate agents, dealers in high value goods such as precious stones and metals or works of art, auctioneers, transporters of funds and casinos.
Includes index.
gau 24/06/14
Loans
Keywords: Money laundering; Banks and banking -- Records and correspondence -- Law and legislation -- Criminal provisions